Naturally occurring benzophenones and xanthones from Garcinia smeathmannii (Planch. & Triana) Oliv. displayed anti-inflammatory effects by modulating the activities of inflammatory mediators in LPS-stimulated RAW 264.7 macrophages - Jeelani, Mohammed; Fouotsa, Hugues; Mohammed, Osama A.; Alfaifi, Jaber; Adebayo, Salmon; Ahmed, Mohammad Muzammil; Yahia, Amar Ibrahim Omer; Eissa, Hanan; Bahashwan, Emad; Mohammed, Nahid Ahmed; Alotaibi, Yousef Ayesh; Asiri, Ashwaq Yahya; et al. (Frontiers in Pharmacology, 2024)
There is a growing interest in studying natural products for the identification of novel lead compounds for drug development for treating inflammatory diseases. Although some studies have focused antiinflammatory activity of benzophenones and xanthones, exploring additional targets such as enzymes and cytokines, involved in their inflammatory response could provide more comprehensive understanding of the compounds' anti-inflammatory effects. In this study, four xanthones ananixanthone (1), smeathxanthone A (2), smeathxanthone B (3), and1,3,5,8-tetrahydroxy-2-(3methybut-2-enyl)-4-(3,7-dimethyloct-2,6-dienyl) xanthone (4); and three benzophenones guttiferone O (5), guttiferone M (6), and aristophenone A (7) from Garcinia smeathmannii (Planch. & Triana) Oliv. were investigated for their effect on nitric oxide production, cyclooxygenase, lipoxygenase inhibition, and Th1/Th2 cytokines production in activated RAW 264.7 macrophages. The Griess reagent method and the ferrous oxidation-xylenol orange assay were used to evaluate the inhibition of NO production and the 15-lipoxygenase activity respectively. Cyclooxygenase activity was assessed using the fluorometric COX activity assay kit and measurement of Th1/Th2 cytokines was performed using a flow cytometer. All the tested compounds exhibited a dose-dependent inhibition of NO production with varying degrees of inhibitory effects on 15-LOX activity. Compound (6), displays the best inhibitory effect on COX-1/COX-2 activity. A general trend of the tested compounds on cytokines profiles revealed that compound (5) showed a pronounced enhancement of anti-inflammatory cytokines (IL-4 and IL-10). This observation supports future exploration of ananixanthone (1), guttiferone O (5), and guttiferone (6) as potential candidates for the development of anti-inflammatory drugs.